Fonetik dalam Bahasa Arab - Reysha Miranti; Althaf Rifqi Alfarabi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Phonetics is a branch of linguistics that studies the sounds of language, including how these sounds are produced, transmitted and received by listeners. In Arabic, phonetics has an important role in understanding how to pronounce sounds correctly. Arabic has a distinctive sound system consisting of vowels, consonants and semivowels, which are produced through various makhraj (places where sounds come out) in the human speech apparatus. Vowel sounds are produced without air resistance, while consonants involve resistance to certain speech organs. Apart from that, Arabic also has letters which are divided into hams (without vibration of the vocal cords) and jahr (with vibration of the vocal cords). Arabic phonetics is very important for improving pronunciation and understanding the meaning of words or sentences, because differences in pronunciation can affect the intended meaning. Therefore, phonetics is an important basis for understanding and practicing Arabic correctly.